UNICEF UK Baby Friendly Initiative: Providing, receiving and leading infant feeding care in a hospital maternity setting-A critical ethnography - Anna Byrom; Gill Thomson; Mark Dooris; Fiona Dykes (Wiley, 2021)
Abstract Although breastfeeding is known to improve health, economic and environmental outcomes, breastfeeding initiation and continuation rates are low in the United Kingdom. The global WHO/UNICEF Baby Friendly Hospital Initiative (BFHI) aims to reverse declining rates of breastfeeding by shifting the culture of infant feeding care provision throughout hospital maternity settings. In the United Kingdom, the global BFHI has been adapted by UNICEF UK reflecting a paradigm shift towards the experiences of women and families using maternity services. This research used a critical ethnographic approach to explore the influence of the national UNICEF UK Baby Friendly Initiative (BFI) standards on the culture of one typical maternity service in England, over a period of 8 weeks, across four phases of data collection between 2011 and 2017. Twenty‐one staff and 26 service users were recruited and engaged in moderate‐level participant observation and/or guided interviews and conversations. Basic, organising and a final global theme emerged through thematic network analysis, describing the influence of the BFI on providing, receiving and leading infant feeding care in a hospital maternity setting. Using Antonovsky's sense of coherence construct, the findings discussed in this paper highlight how the BFI offers 'informational' (comprehensible), 'practical' (manageable) and 'emotional' (meaningful) support for both staff and service users, strengthened by effective, local leadership and a team approach. This is juxtaposed against the tensions and demands of the busy hospital maternity setting. It is recommended that ongoing infant feeding policy, practice and leadership balance relational and rational approaches for positive infant feeding care and experiences to flourish.